Effect of He-Ne Laser on Blood Serum Testosterone and Testicular Tissue in Adult Male Rat - Qader, Nazhad H.; Meikha, Nadem H.; Ali, Basheer M. (Science Journal of University of Zakho, 2016)
The current study was conducted to examine the effect of He-Ne laser therapy on the blood serum testosterone level and testicular tissue in adult male rats. Thirty five Albino Western adult male rats aged 3-4 months and weighing approximately 250-300 g were used and divided in to three groups. The  testicular tissue of rats in the first treatment was exposed to a dose of irradiation 1.02 j/cm2 (40 second) once daily for three successively days, while second treatment was exposed to a dose of irradiation 2.03 j/cm2 (80 second) once daily for three successive date, while the third group remained without any treatments (control).  The results showed that the process of irradiation adversely affected on the level of blood serum testosterone in the first and second treatment compared to the normal level in the control group. The histological examination in treatment one showed  low reduction in numbers of sertoli , leydig  and spermatid cells   at day one, while in day two  showed medium reduction in numbers of sertoli , leydig  and spermatid cells,and high reduction in numbers of sertoli , leydig  and spermatid cells  in day three of irradiation. In treatment two, the results showed   medium reduction in numbers of sertoli , leydig  and spermatid cells at day one, while in day two  showed high reduction in numbers of sertoli , leydig  and spermatid cells and very high reduction in numbers of sertoli , leydig  and spermatid cells in day three of irradiation . In conclusion the current study revealed that steers factor cause reduction in numbers of sertoli , leydig  and spermatid cells  lead to  low fertility rate within  increasing of duration and repetition of irradiation.
Keywords: He-Ne laser; Rats; Testosterone